Conversational competence in Spanish as a foreign language discipline at Universidad de Oriente: diagnosis of its current state - Rivero Cruz, Lizandra; Tardo Fernández, Yaritza (Transformación, 2024)
Objective: To diagnose the teaching-learning process of conversational competence in the discipline of Spanish as a Foreign Language (ELE) at the Universidad de Oriente to achieve a sound approach to the scientific research of its dynamics.Methods: Observation of teaching activities, surveys to foreign students at B2 and C1 levels and documentary review of the programs and didactic materials used for teaching.Result: Several difficulties in Spanish as a foreign language students’ conversational skills were revealed using language assessment tools. This situation hinders the communicative performance of these students in the socio-cultural context in which they learn the Spanish language.Conclusion: The limitations in the teaching-learning process of conversational competence result from a didactic approach that is loosely articulated to the real communication needs of foreign students who learn Spanish in socio-cultural contexts of immersion. The didactic actions use in the teaching practice give insufficient priority conversational training, a situation that demands urgent attention.
Keywords: Second language instruction; competence; conversational skills; skill assessment; language development